2004
DOI: 10.1080/09674845.2004.11732650
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte autoantibodies and expression of CD59 on the surface of red blood cells of polytransfused patients with ß-thalassaemia major

Abstract: Repeated transfusions for the treatment of thalassaemia major cause an insult to the patient's immune system and provoke post-transfusion purpura and haemolytic reactions that can be severe and life threatening. This study aims to investigate the presence of erythrocyte autoantibodies and CD59 expression on the surface of red blood cells (RBCs) in patients with beta-thalassaemia major, and any relationship to frequency of blood transfusion. The study looks at a total of 49 patients (both children and adults) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Unlike PNH, the quantity of CD55 and CD59 on sickle cells is normal; Test & Woolworth (1994) suggested that there may be a functional defect of CD59. It is of interest to note that some patients with thalassaemia suffer from ‘hyperhaemolysis’ (Sirchia et al , 1997) and their RBCs have also been shown to have similar findings concerning CD59 and cytolytic C5b‐9 (Malasit et al , 1997; Salama et al , 2004). Hyperhaemolysis has also been observed in some patients with chronic diseases other than heamoglobinopathies (Treleaven & Win 2004; Darabi & Dzik, 2005) but CD55/59 were not studied in these reports.…”
Section: Novel Mechanisms That May Explain Some Of the Discrepancies mentioning
confidence: 99%
“…Unlike PNH, the quantity of CD55 and CD59 on sickle cells is normal; Test & Woolworth (1994) suggested that there may be a functional defect of CD59. It is of interest to note that some patients with thalassaemia suffer from ‘hyperhaemolysis’ (Sirchia et al , 1997) and their RBCs have also been shown to have similar findings concerning CD59 and cytolytic C5b‐9 (Malasit et al , 1997; Salama et al , 2004). Hyperhaemolysis has also been observed in some patients with chronic diseases other than heamoglobinopathies (Treleaven & Win 2004; Darabi & Dzik, 2005) but CD55/59 were not studied in these reports.…”
Section: Novel Mechanisms That May Explain Some Of the Discrepancies mentioning
confidence: 99%
“…Alloimmunization against red blood will increase the need for blood transfusions in patients with thalassemia. Some alloantibodies are hemolytic and may cause hemolytic transfusion reactions and limit the availability of further safe transfusion but others are clinically insignificant [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the risks of alloimmunization against transfused RBC alloantigens are complex and also depend on the recipient's immune status and the immune modulatory effect of the transfused RBCs on the recipient . Other risk factors reported are the age at initial transfusion, the number of units transfused, age, sex, genetic background, and environmental factors …”
mentioning
confidence: 99%